2020
DOI: 10.3389/fbioe.2020.00176
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated With Colon Cancer: New Potential Prognostic Markers and Targets for Therapy

Abstract: MicroRNAs (miRNAs) are a kind of non-coding RNA (ncRNA) that regulate the expression of target genes and play a role in the occurrence and development of cancers. Colon cancer (COAD) is the second most common cause of cancer-related mortality. However, the prognostic value of miRNAs in COAD is still confusing. In this study, we obtain miRNAs and messenger RNAs (mRNAs) expression profiles of COAD from the Cancer Genome Atlas (TCGA) database. After preliminary data screening and preprocessing, we acquire the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Experiments had demonstrated that miRNAs are closely related to the proliferation, migration, and invasion, and circRNAs can regulate these processes via miRNAs in ccRCC [26][27][28] . Some www.nature.com/scientificreports/ studies also demonstrated that circRNA/miRNA has a strong association with diseases, especially with cancer, by utilizing advanced computational methods such as KATZ algorithm, Locality-Constrained Linear Coding algorithm, inductive matrix completion, decision tree [29][30][31][32][33][34][35] . Therefore, circRNAs and miRNAs can apply as a therapeutic method or a biomarker of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments had demonstrated that miRNAs are closely related to the proliferation, migration, and invasion, and circRNAs can regulate these processes via miRNAs in ccRCC [26][27][28] . Some www.nature.com/scientificreports/ studies also demonstrated that circRNA/miRNA has a strong association with diseases, especially with cancer, by utilizing advanced computational methods such as KATZ algorithm, Locality-Constrained Linear Coding algorithm, inductive matrix completion, decision tree [29][30][31][32][33][34][35] . Therefore, circRNAs and miRNAs can apply as a therapeutic method or a biomarker of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the pursuit of knowledge regarding CRC, the Cancer Genome Atlas (TCGA) database has stored more than 20 cancer genome data types, including mutations, copy number variations, mRNA expressions, miRNA expressions, and methylation data, which are widely used in cancer research [ 4 ]. To date, the TCGA has confirmed nine miRNAs and five genes that have prognostic value in colon cancer [ 5 ]. Therefore, it is vital to identify novel markers for CRC diagnosis and prognosis and provide new targets for CRC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We considered p < 0.05 statistically significant. Using the STRING database, 5 we downloaded data from the PPI network for targeted mRNAs for the hub miRNAs applying the following criteria: (a) homo sapiens; and (b) medium confidence 0.400 ( Zhu et al, 2020 ). Then, the PPI network was further adjusted using the Cytoscape software version 3.7.0, and we identified the top ten key mRNAs of the PPI network using cytoHubba’s Maximal Clique Centrality (MCC) ranking ( Yang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%